The Impact of Knowledge Sharing Behavior on Project Team Performance: Mediating Role of Project Team Effectiveness - Sayyam; Muhammad Tahir Khan; Dr. Muhammad Adil; Raheen Begum (Journal of Business & Tourism, 2021)
The purpose of the study was to explore the influence of Knowledge Sharing Behavior (KSB) on the Protect Team Performance (PTP). The study also determines the mediating role of Project Team Effectiveness (PTE). The existing study shows that population includes the employees of different Project based organization in the twin cities of Peshawar and Mardan. The study was carried out with a cross-sectional survey in the target cities. The study contains of 193 and the data was gathered through an adopted questionnaire. In the present study the covariance sampling technique of the non-probability sampling was used. The gathered data was coded and run via various statistical techniques such as reliability analysis, CFA, descriptive statistics, correlation analysis,and the regression analysis was done by using the Preacher and Hayes (2004) process macro for mediating analysis. Consequently thereafter, the results revealed that Knowledge Sharing Behavior of the protect team and managers in these organizations is positively and significantly associated with Project Team Performance. The study further displays that Project Team Effectiveness is partially mediate the relation between Knowledge Sharing Behavior and Project Team Performance. The study significantly contributes in literature that the effects of Knowledge Sharing Behavior in project based organizations eventually increases the sense in the team members and it triggers proactive working behavior within ethical standards that eventually leads toward improved project team performance. The findings of the study established that Knowledge Sharing Behavior and Project Team Effectiveness have significant impact toward providing Project Team Performance. In further research the impact of Knowledge Sharing Behavior on Project Team Performance can also be identified by using other variables.